1994
DOI: 10.1212/wnl.44.6.1120
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIV‐1 and interleukin‐6 in lumbosacral dorsal root ganglia of patients with AIDS

Abstract: We examined the immunopathology and the expression of human immunodeficiency virus type 1 (HIV-1) in lumbosacral dorsal root ganglia (DRGs) from 16 patients with acquired immunodeficiency syndrome (AIDS) and 10 HIV-1-seronegative controls. Using in situ hybridization, we detected HIV-1 RNA in a few perivascular cells in DRGs from five of 16 AIDS patients (31%). In addition, using polymerase chain reaction, we detected HIV-1 DNA more frequently in DRGs from four of five AIDS patients (80%) examined. We detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…These findings suggest that there is a common indirect cytotoxic mechanism for both DSP and vacuolar myelopathy, which leads to myelin and axonal damage [12]. The presence of Nageotte nodules (cellular proliferations comprised mainly of lymphocytes and activated macrophages) in DRG reinforces the theory of cytokine-mediated indirect mechanisms in HIV neuropathogenesis [13][14][15][16].…”
Section: Indirect Mechanisms Of Hiv Neuropathymentioning
confidence: 54%
“…These findings suggest that there is a common indirect cytotoxic mechanism for both DSP and vacuolar myelopathy, which leads to myelin and axonal damage [12]. The presence of Nageotte nodules (cellular proliferations comprised mainly of lymphocytes and activated macrophages) in DRG reinforces the theory of cytokine-mediated indirect mechanisms in HIV neuropathogenesis [13][14][15][16].…”
Section: Indirect Mechanisms Of Hiv Neuropathymentioning
confidence: 54%
“…This disruption enhances the transendothelial migration of monocytes into the brain which increases the viral reservoir and inevitably effects cognitive, behavioral and motor impairments in HAD. Neuronal death can accompany increased viral replication, particularly in the cortex, the limbic system, and the basal ganglia (Weis et al, 1993;Wiley et al, 1991;Yoshioka et al, 1994). Interestingly, the absolute numbers of immunologically competent brain macrophages and microglia in the CNS, and not the levels of viral expression, appear to be the best predictor of neurologic impairments (Asare et al, 1996;Glass et al, 1995;Glass et al, 1993).…”
Section: Hiv-1 Infection and Activation Of Microglia Leads To Neuronamentioning
confidence: 99%
“…The presence of HIV-infected perivascular macrophages has been shown in the DRG of patients with and without DSP. These studies demonstrated the presence of HIV proviral DNA, mRNA, p24 antigen in these cells [28][29][30][31]. Another consistent neuropathological abnormality in the DRG appears to be the presence of activated macrophages, which express MHC antigens and pro-inflammatory cytokines [4, 29,31].…”
Section: Hiv-dspmentioning
confidence: 99%